Investigation of biodiesel-drive glycerol conversion to polyglycerol over basic modified AlPC catalyst - Ayoub, M. (Asian Research Publishing Network, 2016)
Energy, in the form of biofuel production through transesterification of vegetable oils and animal fats is rapidly increasing due to the hasty outgrowth of population and urbanization. Correspondent increase in the production of crude glycerol causes mixed effects. Sustainable biodiesel production requires optimization of its production process and drastic increase in the utilization of glycerol. To ensure high biodiesel yields and low environmental impacts, with respect to needless waste streams. Upgrading of crude glycerol to highly pure glycerol and subsequent utilization in producing value added products are emerging research areas. The production of such value-added chemicals requires new basic heterogeneous catalysts as well as optimization of the conventional catalyst materials. The clay especially mesoporous type clay have great potential as a catalyst. For present study Aluminum pillared clay (AlPC) was prepared by Al13 precursors and treated with NaOH to modify as basic which enhance conversion of glycerol to polyglycerol (diglycerol, triglycerol). The modified AlPC samples were well characterized by different latest techniques. The modified ALPC was found stable with high mesoporousity and basicity that enhances etherification reaction. The glycerol conversion and polyglycerol production yield was noted maximum 98 and 80.5 over prepared stable modified AlPC catalysts respectively. Industrially, the findings attained in this study might contribute towards promoting the biodiesel industry through utilization of its by-products. Â© 2006-2016 Asian Research Publishing Network (ARPN).